Identification and Validation of Major Cardiovascular Events in the United Kingdom Data Sources Included in a Multi-database Post-authorization Safety Study of Prucalopride - Ruigómez, Ana; Plana, Estel; Gilsenan, Alicia; Fortuny, Joan; Cainzos-Achirica, Miguel; Flynn, Robert W. V.; MacDonald, Thomas M.; Garcia-Rodriguez, Luis; Ziemiecki, Ryan; Andrews, Elizabeth B. (Drug safety, 2021)
Introduction A multinational post-authorization safety study assessed cardiovascular safety in initiators of prucalopride for chronic constipation compared with a matched cohort of polyethylene glycol 3350 initiators. The primary safety outcome was major adverse cardiovascular events (MACE), a composite of hospitalization for acute myocardial infarction, stroke, or in-hospital cardiovascular death. We report the validation process for MACE endpoints in United Kingdom (UK) data sources: Clinical Practice Research Datalink (CPRD GOLD), The Health Improvement Network (THIN), and the Information Services Division (ISD) Scotland. Methods Modified electronic algorithms from prior research identified potential MACE cases. Validation followed a common protocol, adapted for each database, with all information anonymized: (1) direct confirmation via linkage to hospital records (CPRD GOLD); (2) requests for additional clinical information through questionnaires (CPRD GOLD), free-text (THIN), or abstraction of hospital records (ISD); (3) manual review of electronic records of potential events retrieved by the algorithm (CPRD GOLD/THIN); and (4) event adjudication by three clinicians, blinded to exposure, for all remaining events. Results Electronic algorithms identified 260 potential MACE cases: 38 confirmed via linkage to hospital records (CPRD GOLD), 56 ruled out as non-cardiovascular death cases (THIN), and three unavailable for review (ISD), leaving 163 potential cases. After manual review with additional information (steps 2 and 3), 45 were considered noncases (CPRD GOLD/THIN). Upon final adjudication (step 4), remaining potential events were adjudicated as definite ( n = 62), probable ( n = 10), possible ( n = 13), or noncases ( n = 33). Conclusions Given the limitations of relying solely on computer algorithms to identify cardiovascular outcomes, validation with clinical review is essential to guide interpretation.